2007
DOI: 10.1002/lapl.200710082
|View full text |Cite
|
Sign up to set email alerts
|

Selective ablation of dental enamel and dentin using femtosecond laser pulses

Abstract: The study of the interaction of intense laser light with matter, as well as transient response of atoms and molecules is very appropriated because of the laser energy concentration in a femtosecond optical pulses. The fundamental problem to be solved is to find tools and techniques which allow us to observe and manipulate on a femtosecond time scale the photonics events on and into the matter. Six third human extracted molars were exposed to a femtosecond Ti:Sapphire Q-switched and mode locked laser (Libra-S, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 24 publications
2
60
0
2
Order By: Relevance
“…In this way, it is easier to adjust a laser fluence that can be bellow or above the ablation threshold of a specific material. Literature studies determined that the threshold fluence for ablating enamel with USPL is higher than the fluence for ablating dentin and, in the same way that using erbium lasers, it is easier and faster to ablate dentin than enamel, which suggests selectivity to the tissue removal (Lizarelli et al, 2008;Niemz et al, 2004;Strassl et al, 2008;Wieger et al, 2006;). In 2006, Wieger et al used a picosecond Nd:YVO 4 laser for ablation of sound dentin, and it was observed the production of a microretentive pattern with opened tubules and the absence of microcracks or melting.…”
Section: The Use Of Ultra Short Pulse Lasers (Uspls) In Dentistrymentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, it is easier to adjust a laser fluence that can be bellow or above the ablation threshold of a specific material. Literature studies determined that the threshold fluence for ablating enamel with USPL is higher than the fluence for ablating dentin and, in the same way that using erbium lasers, it is easier and faster to ablate dentin than enamel, which suggests selectivity to the tissue removal (Lizarelli et al, 2008;Niemz et al, 2004;Strassl et al, 2008;Wieger et al, 2006;). In 2006, Wieger et al used a picosecond Nd:YVO 4 laser for ablation of sound dentin, and it was observed the production of a microretentive pattern with opened tubules and the absence of microcracks or melting.…”
Section: The Use Of Ultra Short Pulse Lasers (Uspls) In Dentistrymentioning
confidence: 99%
“…Considering the advances in technology for the development of ultra short pulse lasers (USPLs) (Niemz, 1995;Strickland & Mourou, 1985), efforts have been implemented to understand their interaction with dental hard tissues and to determine safe and proper parameters to provide a future clinical application in dentistry (Altshuler et al, 1994;Freitas et al, 2010;Kruger et al, 1999;Lizarelli et al, 2008;Strassl et al, 2008). Due to the extremely short pulse length, these systems promote precise cutting and have a strong potential for obtaining well-defined cavities and controlled caries removal (Niemz, 2004;Serbin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The use of lasers in the medical field, as an instru ment for contact free tissue removal of dental hard tis sues [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], osseous tissues [33][34][35] have been stud ied as a means for complementing conventional drill ing or cutting tools. In all applications, a balance between several phenomena must be taken into con sideration.…”
Section: Introductionmentioning
confidence: 99%
“…The use of ultrafast laser pulses is having an impact on materials and processing in biological tissues in a profound ways [1][2][3][4][5][6][7]. Laser precision engineering is being extensively applied in industries for device micro fabrication due to its unique advantages of being a dry and noncontact process, coupled with the availability of reliable light sources and affordable system cost [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…When femtosecond laser pulses are tightly focused within a transparent bulk material, nonlinear absorption can be induced in the focal volume and 1 The article is published in the original. lead to highly localized energy deposition resulting in a range of possible changes in material properties [19].…”
Section: Introductionmentioning
confidence: 99%